2017
DOI: 10.1007/s10103-017-2321-8
|View full text |Cite
|
Sign up to set email alerts
|

The effect of laser power, blood perfusion, thermal and optical properties of human liver tissue on thermal damage in LITT

Abstract: In this work, the finite-element method (FEM) was used to predict the temperature distribution, and the thermal damage volume in human liver tissue subjected to laser in laser-induced interstitial thermotherapy (LITT). The effect of laser power, blood perfusion, and thermal and optical properties on maximum temperature and thermal damage volume were predicted using the finite-element method. A computer program was written in visual basic language, which was verified by comparing its result with data published … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…Therefore, if the laser is like a lancet, the average power is the amount of force used to operate the lancet. It has been confirmed that liver excision using laser entails the conversion of light energy into heat to coagulate liver tissue [29,30]. Higher heat energy leads to a better coagulation effect, resulting in better liver cutting speed and hemostasis effect; however, greater heat also worsens thermal damage.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, if the laser is like a lancet, the average power is the amount of force used to operate the lancet. It has been confirmed that liver excision using laser entails the conversion of light energy into heat to coagulate liver tissue [29,30]. Higher heat energy leads to a better coagulation effect, resulting in better liver cutting speed and hemostasis effect; however, greater heat also worsens thermal damage.…”
Section: Discussionmentioning
confidence: 99%
“…. As the Lagrangian is linear in p and ψ, we see that equations (8) and (9) of the optimality system are equivalent to the state equations (1) and (2) that constrain the optimization problem (5).…”
Section: Adjoint-based Identificationmentioning
confidence: 99%
“…The knowledge of the location of the blood vessels in the vicinity of tumorous tissue (and, thus, close to the applicator) is crucial for the performance of the therapy as well as for the reliability of a simulation model as e.g. discussed in [1][2][3][4][5]. Unfortunately, the location relative to the applicator varies for each patient and treatment.…”
Section: Introductionmentioning
confidence: 99%
“…where A, E a , and R a are the frequency factor, activation energy, and universal gas constant, respectively. For liver thermal damage, A = 9.4 × 10 104 s −1 , E a = 6.68 × 10 5 J mol −1 , and R a = 8.31 J mol −1 K −1 [23]. The undamaged fraction of the tissue and the damaged fraction can be estimated by f u = exp(−Ω) and f d = 1 − f u , respectively [24].…”
Section: Thermal Energy Model For Tissue Heatingmentioning
confidence: 99%
“…where W b,0 is the constitutive blood perfusion rate, 18.2 Kg m −3 s −1 for liver, and f T is a dimensionless function that accounts for vessel dilation at slightly elevated temperatures, which can be approximated as [23,24]:…”
Section: Dynamic Tissue Propertiescmentioning
confidence: 99%